Suffering as a means to enhance experiential learning - Maykut, Colleen; Porter, Meredith (My University, 2015)
The aim of this study was to examine the efficacy of a combined teaching and learning strategy (vodcast and narratives) to replace a traditional lecture to enhance experiential learning focusing on the concepts of caring, suffering, and ethical dilemmas.
Keywords: caring; nursing education; narrative learning; suffering; vodcast